A density-dependent failure criterion for concrete. (15th October 2016) - Øverli, Jan Arve
Highlights: An octahedral failure criterion for concrete. Includes the density of the concrete directly in the failure criterion. For low densities the compressive and tensile meridian tends toward a single curve. Abstract: This work focuses on the large effect of small secondary stresses on the compressive strength of concrete. The strength and especially the ductility of structural concrete members depend on local triaxial stress conditions that inevitably develop in the compressive zone just prior to failure. A failure criterion for concrete, which accounts for the effect of a reduced density of the concrete on the strength under fully compressive triaxial stress states, is proposed. The criterion was derived by curve-fitting mathematical expressions to axisymmetric strength data from a test programme on concretes of different weights previously published. For the purpose of evaluation, it was compared to other triaxial compressive strength data for lightweight aggregate concrete available in the literature; and to the failure criterion in fib Model Code 2010. It was found that, contrary to the Model Code criterion, the failure criterion presented in this paper generally provides safe lower bound estimates for the strength levels attained in the experimental tests.